The all-sky-6 and the Video Meteor Archive system of the AMS Ltd. (1st October 2020) - Hankey, Mike; Perlerin, Vincent; Meisel, David
Abstract: Over a period of several years, the American Meteor Society, Ltd. (AMS) has developed a custom hardware and software system for capturing, reducing, solving and permanently storing meteor event data along with all-important corroborating video media from which high accuracy and reliable information can be gleaned. The connected hardware and software developed for trajectory analysis up to this point has utilized mainly open source materials and steadily matured into a modern, online system with wide international connections through "live" internet interactions between the various camera stations. Some critical software components and algorithms used by our system for the astrometric calibration of the cameras as well as trajectory and orbit solving have been developed by Denis Vida and provided through his RMS (Raspberry Pi Meteor Station) and WMPL (Western Meteor Python Library) open-source projects. These routines and solvers are currently integrated into the AMS routine workflow along with some others from the open or published literature. A continuing check of our computational integrity during the rather difficult atmospheric trajectory stage is obtained by "back" solving those relatively rare concurrent events where there has been camera detection overlap with those objects formally published by other networks and available openly online. The trajectory part of the solution is the most difficult part of the process to automate and verify with a minimum of human intervention and so that part of the entire computational process is still in beta testing. On the other hand, the strongly autonimous computation of going from meteor trajectory to orbital elements through our version of WMPL has been tested against the listed online orbital elements derived with the same trajectory information (URL here) and is discussed in some detail statistically. We are continuing to search for instrumental causes and possible remediation of trajectory characterization faults and errors whether between stations or between individual cameras before we move our system out of the current beta testing phase.